Chemical exchange saturation transfer MRI serves as predictor of early progression in glioblastoma patients - Regnery, Sebastian; Adeberg, Sebastian; Dreher, Constantin; Deike-Hofmann, Katerina; Bickelhaupt, Sebastian; Radbruch, Alexander; Bendszus, Martin; Wick, Wolfgang; Unterberg, Andreas; Rieken, Stefan; Debus, Jürgen; Bachert, Peter; et al. (OncoTarget, 2018)
Oncotarget | https://doi.org/10.18632/oncotarget.25594 Sebastian Regnery, Sebastian Adeberg, Constantin Dreher, Johanna Oberhollenzer, Jan-Eric Meissner, Steffen Goerke, Johannes Windschuh, Katerina...
Gesehen am 12.12.2019